The reliability and usefulness of a novel basketball standardized shooting task - Daub, B. D.; McLean, B. D.; Heishman, A. D.; Coutts, A. J. (International Journal of Sports Science & Coaching, 2023)
The purpose of this investigation was to develop a basketball shooting performance test and subsequently assess the tests measurement characteristics and construct validity. The novel standardized shooting task (SST) was comprised of 60 free throw attempts followed by a 4-min spot-to-spot shooting segment (including seven sequential locations either outside the 3-point line or at a 15-foot mark, depending upon player role). After development of the SST, 28 (male = 16, female = 12) NCAA Division I basketball players completed the task on separate days (Part 1; reliability) and then following a standard basketball practice (Part 2; sensitivity). SST performance collected from 13 males was then compared with shots made during live practices and expert ranking's (Part 3; construct validity). Interday reliability (Part 1) measures were: intraclass correlations coefficient = 0.77-0.86; coefficient of variation = 1.9-12.0%. There were no significant differences (p>0.05) between days for any performance variables. From pre- to post-practice (Part 2) repeated measures analyses of variance showed a significant difference (p = 0.03) for shots made in 4-min (MAKE4MIN; pre = 51.6 ± 8.8, post practice = 48.7 ± 9.3), while no significant differences were detected for any other variables. Results from Part 3 indicated large correlations for Shooter Rank versus MAKE4MIN (r = 0.814, p = 0.001) and Shooter Rank versus shooting percentage in live play (r = 0.815, p = 0.001). These data demonstrate the SST poses sufficient reliability and sensitivity to detect meaningful changes in performance, as well as adequate construct validity. Therefore, offering an ecologically valid measurement which can be incorporated to athlete monitoring strategies in elite basketballers.